Survey Kepuasan Pengguna Jasa Pelayanan Kesehatan Perjan Rumah Sakit Sanglah Denpasar = Sanglah Hospital Customer Satisfaction Survey - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Background: Sanglah Hospital wants to be a market leader in health care services in Bali. Reaching this objective, they should improve the performance of their medical units by doing a satisfaction survey using a servqual approach model by Pasuraman. Method: 395 hospital patients selected among those who visited the hospital. Adjusted number of randomly selected samples has been applied according to the proportion of reported client visited each medical unit. Average 640 patients were visited this hospital everyday. The sample consist of 150 hospitalized patients (38%), 188 outpatient clinic patients (47, 6%), and 57 emergency unit patients (14, 4%). Respondent were patient or his/her care givers who was waiting for him or her. They completed a pair of questionnaires consist of 20 variables developed. Result: In general, Sanglah hospital clients were not satisfied with the staff performance. Level of adjustment was 84.96%. The hospital management should highly recommended to improve nursing staff skilled, quality assurance, client s belief, and service equity disregard of socio-economic status, completeness of medical instruments, staff readiness and room cleanness. Linear regression analysis showed that empathy and reliability were ranked highly as two contributing factor related to client satisfaction variation (r2= 0,158 and r2= 0,009). Conclusion: Patient satisfaction was still under client s expectation. Nursing staff skill and quality of care assurance should be improved by hospital management for better staff performance.